Selina solutions

Selina solutions

Grade 6

Simple (Linear) Equations (Including Word Problems) | Exercise 22(A)

Question 1

Q1) Solve:

(i) x + 2 = 6

(ii) x + 6 = 2

(iii) y + 8 = 5

(iv) x + 4 = - 3

(v) y + 2 = - 8

(vi) b + 2.5 = 4.2

(vii) p + 4.6 = 8.5

(viii) y + 3.2 = - 6.5

(ix) a + 8.9 = - 12.6

(x) x + 2\frac{1}{3} = 5

(xi) z + 2 = 4\frac{1}{5}

(xii) m + 3\frac{1}{2}=4\frac{1}{4}

(xiii) x + 2 = 1\frac{1}{4}

(xiv) y + 5\frac{1}{3}= 4

(xv) a + 3\frac{1}{5}=1\frac{1}{2}

Solution 1:

(i) x + 2 = 6

x = 6 - 2

x = 4

(ii) x + 6 = 2

x = 2 - 6

x = -4

(iii) y + 8 = 5

y = 5 - 8

y = -3

(iv) x + 4 = -3

x = -3 -4

x = -7

(v) y + 2 = -8

y = -8 -2

y = -10

(vi) b + 2.5 = 4.2

b = 4.2 - 2.5

b = 1.7

(vii) p + 4.6 = 8.5

p = 8.5 - 4.6

p = 3.9

(viii) y + 3.2 = -6.5

y = -6.5 -3.2

y = -9.7

(ix) a + 8.9 = -12.6

a = -12.6 -8.9

a = -21.5

(x) x + 2\frac{1}{3} = 5

x + \frac{7}{3}=5

x = 5-\frac{7}{3}=\frac{15-7}{3}=\frac{8}{3}

x = 2\frac{2}{3}

(xi) z + 2 = 4\frac{1}{5}

z + 2 = \frac{21}{5}

z = \frac{21}{5}-2=\frac{21-10}{5}=\frac{11}{5}

z = 2\frac{1}{5}

(xii) m + 3\frac{1}{2}=4\frac{1}{4}

m + \frac{7}{2}=\frac{17}{4}

m = \frac{17}{4}-\frac{7}{2}=\frac{17-14}{4}=\frac{3}{4}

(xiii) x + 2 = 1\frac{1}{4}

x + 2 = \frac{5}{4}

x = \frac{5}{4}-2=\frac{5-8}{4}=\frac{-3}{4}

x = -\frac{3}{4}

(xiv) y + 5\frac{1}{3}= 4

y + \frac{16}{3}=4

y = 4-\frac{16}{3}=\frac{12-16}{3}=\frac{-4}{3}

y = -1\frac{1}{3}

(xv) a + 3\frac{1}{5}=1\frac{1}{2}

a + \frac{16}{5}=\frac{3}{2}

a = \frac{3}{2}-\frac{16}{5}=\frac{15-32}{10}=\frac{-17}{10}

a = -1\frac{7}{10}

Still have questions? Our expert teachers can help you out

Book a free class now

Want to top your mathematics exam ?

Learn from an expert tutor.

Book a free class now
subject-cta

Question 1

Q1) Solve:

(i) x + 2 = 6

(ii) x + 6 = 2

(iii) y + 8 = 5

(iv) x + 4 = - 3

(v) y + 2 = - 8

(vi) b + 2.5 = 4.2

(vii) p + 4.6 = 8.5

(viii) y + 3.2 = - 6.5

(ix) a + 8.9 = - 12.6

(x) x + 2\frac{1}{3} = 5

(xi) z + 2 = 4\frac{1}{5}

(xii) m + 3\frac{1}{2}=4\frac{1}{4}

(xiii) x + 2 = 1\frac{1}{4}

(xiv) y + 5\frac{1}{3}= 4

(xv) a + 3\frac{1}{5}=1\frac{1}{2}

Solution 1:

(i) x + 2 = 6

x = 6 - 2

x = 4

(ii) x + 6 = 2

x = 2 - 6

x = -4

(iii) y + 8 = 5

y = 5 - 8

y = -3

(iv) x + 4 = -3

x = -3 -4

x = -7

(v) y + 2 = -8

y = -8 -2

y = -10

(vi) b + 2.5 = 4.2

b = 4.2 - 2.5

b = 1.7

(vii) p + 4.6 = 8.5

p = 8.5 - 4.6

p = 3.9

(viii) y + 3.2 = -6.5

y = -6.5 -3.2

y = -9.7

(ix) a + 8.9 = -12.6

a = -12.6 -8.9

a = -21.5

(x) x + 2\frac{1}{3} = 5

x + \frac{7}{3}=5

x = 5-\frac{7}{3}=\frac{15-7}{3}=\frac{8}{3}

x = 2\frac{2}{3}

(xi) z + 2 = 4\frac{1}{5}

z + 2 = \frac{21}{5}

z = \frac{21}{5}-2=\frac{21-10}{5}=\frac{11}{5}

z = 2\frac{1}{5}

(xii) m + 3\frac{1}{2}=4\frac{1}{4}

m + \frac{7}{2}=\frac{17}{4}

m = \frac{17}{4}-\frac{7}{2}=\frac{17-14}{4}=\frac{3}{4}

(xiii) x + 2 = 1\frac{1}{4}

x + 2 = \frac{5}{4}

x = \frac{5}{4}-2=\frac{5-8}{4}=\frac{-3}{4}

x = -\frac{3}{4}

(xiv) y + 5\frac{1}{3}= 4

y + \frac{16}{3}=4

y = 4-\frac{16}{3}=\frac{12-16}{3}=\frac{-4}{3}

y = -1\frac{1}{3}

(xv) a + 3\frac{1}{5}=1\frac{1}{2}

a + \frac{16}{5}=\frac{3}{2}

a = \frac{3}{2}-\frac{16}{5}=\frac{15-32}{10}=\frac{-17}{10}

a = -1\frac{7}{10}

Still have questions? Our expert teachers can help you out

Book a free class now

Want to top your mathematics exam ?

Learn from an expert tutor.

Book a free class now
subject-cta
linkedin instgram facebook youtube
2020 © Quality Tutorials Pvt Ltd All rights reserved
linkedin instgram facebook youtube